Penguatan Kapasitas Perempuan Sebagai Agen Perubahan Lingkungan dalam Program Zero Waste Berbasis Komunitas - Ngurah Ayu Dian Anggraeni; Eko Sasono (Carmin: Journal of Community Service, 2025)
This community service activity aims to enhance the capacity and role of women in community-based household waste management through a zero waste approach. The method used is a participatory approach through education, training, and direct practice involving 20 housewives in Simongan, Semarang City. Over two months, participants received materials on waste sorting, compost making, eco enzyme, ecobrick, and creative products from plastic waste. The results show that 80% of the participants started sorting waste, and 65% utilized it productively. Participants are also actively developing functional products and depositing waste at local waste banks. This activity encourages the formation of study groups and women's participation in environmental forums. In conclusion, an educational and participatory approach is effective in shaping environmentally friendly behavior and promoting economic independence. Similar activities have the potential to be replicated in other regions as a strategy for strengthening women's capacity and sustainable community development.